2020
DOI: 10.1038/s41467-020-18484-8
|View full text |Cite
|
Sign up to set email alerts
|

Gradient tantalum-doped hematite homojunction photoanode improves both photocurrents and turn-on voltage for solar water splitting

Abstract: Hematite has a great potential as a photoanode for photoelectrochemical (PEC) water splitting by converting solar energy into hydrogen fuels, but the solar-to-hydrogen conversion efficiency of state-of-the-art hematite photoelectrodes are still far below the values required for practical hydrogen production. Here, we report a core-shell formation of gradient tantalum-doped hematite homojunction nanorods by combination of hydrothermal regrowth strategy and hybrid microwave annealing, which enhances the photocur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
104
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(109 citation statements)
references
References 61 publications
4
104
1
Order By: Relevance
“…Photoelectrochemical impedance spectroscopy (PEIS) was employed to compare the charge transfer processes between Ta 3 N 5 and In:GaN/Ta 3 N 5 /Mg:GaN photoanodes 14,22 . The PEIS Nyquist plots in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoelectrochemical impedance spectroscopy (PEIS) was employed to compare the charge transfer processes between Ta 3 N 5 and In:GaN/Ta 3 N 5 /Mg:GaN photoanodes 14,22 . The PEIS Nyquist plots in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, tremendous efforts have been devoted to interface engineering of various semiconductor photoelectrodes (e.g., Si 20,21 , α-Fe 2 O 3 22 , BiVO 4 23 , Cu 2 O 24 ) to improve their efficiency and stability through the passivation of interfacial defects or formation of hetero-/homojunctions. Ideally, the semiconductor thin film light absorbers should be sandwiched by a n-type electron transport layer (ETL) and a p-type hole transport layer (HTL) to achieve efficient charge separation, similar to the "n-i-p" device architecture commonly used in thin-film photovoltaics 25 .…”
mentioning
confidence: 99%
“…[ 138 , 139 ] Recently, heteroatom doping ( Figure 8 a ) has shown great potential in PEC‐driven catalytic reactions. [ 140 , 141 ]…”
Section: Advancing Pec Reactions Through Atomic Design Of Photoelectrodesmentioning
confidence: 99%
“…In recent years, Ta-TiO2 has been investigated for solar cells 18 , water splitting 19 , corrosion resistance 20 , photovoltaics 17 , wastewater treatment 8 , oxygen reduction reaction 21 , and lithium ion batteries 22 . These reports have shown that Ta could be utilised as an effective additive or dopant to increase the catalytic performance of TiO2.…”
mentioning
confidence: 99%